PENGARUH PENERAPAN GUESSING GAME TERHADAP KEMAMPUAN BERBICARA MAHASISWA STAIN BENGKALIS - Kurniati Kurniati; Ervina Ervina (AL-ISHLAH: Jurnal Pendidikan, 2019)
This study aims to determine the students’ speaking skill before and after applying Guessing Game and find out the effect of Guessing Game on the students’ speaking skill at the first semester of English education study program of STAIN Bengkalis. This research is experimental research that involved 18 students at the first semester of English Education Study Program of STAIN Bengkalis. Speaking test was implemented in order to collect the students’ speaking performance, and the collected data were quantitatively analyzed. Guessing Game has a less significant effect in improving the students’ speaking skill at the first semester of English education study program of STAIN Bengkalis. This is evidenced by the results of t-o (1,3) smaller than t-table.